2017
DOI: 10.1149/2.0161712jss
|View full text |Cite
|
Sign up to set email alerts
|

Through-Silicon via Submount for Flip-Chip LEDs

Abstract: A blue light emitting diode (LED) was prepared by a flip-chip (FC) LED and three-dimensional through-silicon via (3D-TSV) technique. The experimental results indicated that the diameter and length of the Si via were about 180 μm and 400 μm, respectively. The Cu was uniformly and high density filled in each TSV, and the average resistance was about 0.14 m . It was also found that the 96.43Sn-3.57at%Ag bumps were electroplated on the Cu plugged TSVs of a silicon substrate, and these were smoother at 250 • C. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The authors recently reported the fabrication of a 3D LED structure. 5 In this study, the TSV and LED chips are smaller. A 6-inch P-type 350 μm thick Si wafer was wet cleaned in a standard RCA process and used as a lower substrate.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…The authors recently reported the fabrication of a 3D LED structure. 5 In this study, the TSV and LED chips are smaller. A 6-inch P-type 350 μm thick Si wafer was wet cleaned in a standard RCA process and used as a lower substrate.…”
Section: Methodsmentioning
confidence: 84%
“…The respective values for the parameters for the TSV process for the flow of SF 6 gas and O 2 gas, the substrate temperature, z E-mail: tj.hsueh@gmail.com the etching time, the electrode gap, the RF power and the pressure in the chamber were 60 sccm, 5.4 sccm, −117 • C, 150 min, 7 cm, 1000 W and 10 mTorr. 5 Then the barrier layer Al was removed by aluminum etching. An isolation layer SiO 2 with a thickness of 800nm was formed by thermal oxidation.…”
Section: Methodsmentioning
confidence: 99%
“…28 Moore's law is the subject of many studies, which use a throughsilicon via (TSV) technology to fabricate a three-dimensional (3D) integrated circuit (IC). TSV technology is used in electric devices and LED's, 29,30 humidity sensors, 31 photo sensors 32 and field emission. 33 This study produces a 3D room temperature TiO 2 NH 3 gas sensor using TSV technology and atomic layer deposition (ALD).…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12] It is found that the use of FCLEDs is more advantageous than lateral LEDs in achieving high luminous intensity and efficient heat dissipation because photons are extracted through the transparent sapphire substrate and the use of bonding wire is obviated,. [10][11][12][13][14][15] In particular, the removal of wire bonding can increase electrical contact area and reduce current crowding, resulting in a lower forward bias voltage. Furthermore, the deterioration of ray-uniformity caused by the bonding wire can be alleviated.…”
mentioning
confidence: 99%
“…Since the disconnection of bonding wire can result in device failure, the elimination of the wire can eventually improve the reliability of devices. [10][11][12][13][14][15] In FCLED packaging, the thermal resistance of the packaged devices is directly affected by die bonding. Particularly, voids are known to readily form in the solder layers during the manufacturing process [16][17][18] and grow larger as a result of thermal cycles and thermal stress.…”
mentioning
confidence: 99%